Performance of ECDC ILI case definition and ICPC R80 code for influenza surveillance - Pinto Leite, Pedro (2019)
In this study we took advantage of the Portuguese Influenza Surveillance Systems (ISS) database to assess and compare the performance of the two main case definitions used in Portugal: the European Centre for Disease Prevention and Control (ECDC) ILI case definition and the International Classification of Primary Care (ICPC) R80 code.